“The Impact of Participation in The MGNREGS On Beneficiaries-A Study in Select Districts of Telangana” - K. Naveen Kumar, Dr. D. Gnyaneswer, J. Lavanya (Journal of Informatics Education and Research, 2024)
Since backward and rural employment and village development are essential to India's growth, the MGNREGA actively promotes backward and rural development by hiring unskilled labor. The MGNREGA helps BPL families by filling in the gaps in inflation and giving them seasonal work during dry spells. MGNREGS offers beneficiaries a chance to advance their socioeconomic status. Objectives of the present study: To study the impact t of no of years, no of days and daily wages received of beneficiaries on economic, social and living status of beneficiaries. Methodology: the study is depending on primary data source and data is collected with the help of structured schedule. For the study sample size is 364 respondents. The methods used in this research is regression model with help of SPSS. Findings: The result of the study are about 53% of the living status of the beneficiaries is impacted by the daily wages received the impact is also statistical significant and about 70% of the social status of the beneficiaries is impacted by the daily wages received, Suggestions: It is suggested that the wage rates under the MGNREGS need to be revised periodically to improve the living status of the beneficiaries.